2006
DOI: 10.1177/095632020601700602
|View full text |Cite
|
Sign up to set email alerts
|

PAMAM Dendrimers and Branched Polyethyleneglycol (Nanoparticles) Prodrugs of (-)-β-D-(2R, 4R)-dioxolane-thymine (DOT) and Their Anti-HIV Activity

Abstract: The synthesis, characterization, anti-HIV activity and cytotoxicity of dendrimers of (-)-β β-D-(2R,4R)-dioxolane-thymine (DOT) and polyethylene glycol (PEG)-DOT conjugates are described. Dendrimers in this study were polyamidoamine (PAMAM) generation 2.0, 3.0, 5.0 and 6.0, along with 8.0-branched PEG with a molecular weight of 40 kDa. DOT was attached to PAMAM dendrimers or branched PEG via ester or phosphate groups. Size exclusion chromatography was used to purify the dendrimers and PEG conjugates, which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Dendrimers represent an important class of macroions. Due to their spherical shape, low dispersity, pH-dependent charge, flexibility in tuning their molecule structure and size during synthesis they are used in medicine, , electronics, catalysis, or light harvesting …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dendrimers represent an important class of macroions. Due to their spherical shape, low dispersity, pH-dependent charge, flexibility in tuning their molecule structure and size during synthesis they are used in medicine, , electronics, catalysis, or light harvesting …”
Section: Introductionmentioning
confidence: 99%
“…Besides in basic research, PAMAM dendrimers have found application in the industry, e.g., as part of optical and electrochemical sensors, , in size exclusion chromatography, in medicine for pulmonary drug delivery, and in magnetic resonance imaging contrast agent delivery . They can also serve as a platform for adsorption of proteins and drugs …”
Section: Introductionmentioning
confidence: 99%
“…Liang and coworkers [64] evaluated the anti-HIV activity of PAMAM derivatives (the authors designed the compounds using (−)-β- d -(2 R ,4 R )-dioxolane-thymine (a bioactive molecule, named as DOT), PAMAM generations 2.0, 3.0, 5.0 and 6.0, either with or without polyethylene glycol (PEG). The prodrugs were obtained by ester or phosphate linkages, purified by applying exclusion chromatography and characterized using NMR and MALDI-TOF mass spectrometry.…”
Section: General Applications Of Dendrimer Prodrugsmentioning
confidence: 99%